Доклад о Целях в области устойчивого развития, 2020 год - United Nations Department of Economic; Social Affairs (United Nations, 2020)
The Sustainable Development Goals Report 2020 presents how far we have come towards reaching the 17 Sustainable Development Goals (SDGs). This fifth edition of the annual report contains a review of all the 17 Goals. It uses the latest available data and inputs from custodian agencies of the United Nations system other international agencies and is prepared by the Statistics Division of the Department of Economic and Social Affairs.